Exploring Mentoring Practice for In-service Teachers’ Professional Development - Dahal, Gyanu (KMC Journal, 2023)
This study explores how untrained and trained mentors practise mentoring with their mentees and how trained mentors make mentoring practice effective. This study also exhibits the value of teachers’ professional development (TPD) to update teachers’ knowledge and skills. Mentoring is one of the key components of TPD that helps teachers continuously update and upgrade their performance. However, in the Nepalese context, mentoring is taken as an evaluation or judgement. A review of the literature examines mentoring practice by a trained mentor useful for teachers in their professional development. It enables mentee teachers to reflect on their practice. The mentee teacher receives support and feedback from their mentor that helps them to develop meaningful learning experiences. I used a qualitative case study design to study the impact of mentoring practice by trained mentors on the professional development of English language teachers in Nepal. The data drawn from teachers’ reflective journals, semi-structured interviews and mentoring sessions’ notes were collected data and triangulated to produce fair results. The results indicated that for effective mentoring practice, mentors should be trained before practising mentoring for teachers’ professional development.